sj-pdf-19-msj-10.1177_13524585221134213 – Supplemental material for Cerebrospinal fluid kappa free light chains for the diagnosis of multiple sclerosis: A systematic review and meta-analysis - Harald Hegen; Janette Walde; Klaus Berek; Georgina Arrambide; Sharmilee Gnanapavan; Batia Kaplan; Michael Khalil; Ruba Saadeh; Charlotte Teunissen; Hayrettin Tumani; Luisa M Villar; Maria Alice V Willrich; et al. (SAGE Journals, 2022)
Supplemental material, sj-pdf-19-msj-10.1177_13524585221134213 for Cerebrospinal fluid kappa free light chains for the diagnosis of multiple sclerosis: A systematic review and meta-analysis by Harald Hegen, Janette Walde, Klaus Berek, Georgina Arrambide, Sharmilee Gnanapavan, Batia Kaplan, Michael Khalil, Ruba Saadeh, Charlotte Teunissen, Hayrettin Tumani, Luisa M Villar, Maria Alice V Willrich, Henrik Zetterberg and Florian Deisenhammer in Multiple Sclerosis Journal
Keywords: Neurology and Neuromuscular Diseases; Aged Health Care